Intense violet electroluminescence of thin SiO2 layers with SnO2 nanocrystals - Ivan Romanov; Irina Parkhomenko; Liudmila Vlasukova; Elke Wendler; Fadei Komarov (Results in Optics)
It has been shown that Sn implantation with subsequent annealing in air leads to an increase in the electroluminescence (EL) intensity of SiO2/Si structure by two orders of magnitude. Intense violet EL with a maximum at 3.21  eV was observed at room temperature by the naked eye at forward bias. The observed emission was attributed to radiative recombination in SnO2 nanocrystals synthesized in SiO2 layers. The external quantum efficiency (EQE) increased with decreasing Sn concentration The maximum external quantum efficiency was found to be 0.7 % for the silica film Sn-implanted at the lowest fluence of 2.5 × 1016 cm−2. The non-radiative charge transport (shunt current) through the sample and mechanism of EL excitation are discussed. It has been concluded that the Poole–Frenkel mechanism, or tunneling between traps are the most likely mechanisms of charge transport to light-emitting centers.